MOTIVASI KEWIRAUSAHAAN PETANI PADI ORGANIK DI KABUPATEN BANTUL - Nur Ratmawati; Triyono Triyono; Sriyadi Sriyadi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
The  improvement  of  farmers’  welfare,  especially  rice  farmers  require efforts  to  improve  the  ability  of  farmers  to  produce  quality  products  and  which  is competitive. An effort that can be done is to increase the motivation of entrepreneur communities  through  organic  farming  which  can  be  expected  to  ensure  the preservation of the environment for sustainable production, achieve food security at the same time improving the welfare of people that having quality.This research aims to identify the motivation of entrepreneur    farmers and the individual factors and the influence  of  environments.  The  study  was  conducted  by  interview  survey  method  on organic rice farmers, then it was analyzed by descriptive and regression analysis. The results showed that the general motivation of entrepreneur farmers is strong enough. Factors that influence entrepreneurmotivation is the business environment; access to credit, market orientation, a network of cooperation and support from the government as well as individual factors, namely education.